PROFILES OF CARBOHYDRATE LIGANDS ASSOCIATED WITH ADSORBED PROTEINS ON SELF-ASSEMBLED MONOLAYERS OF DEFINED CHEMISTRIES - Shankar, Sucharita P. (J Biomed Mater Res A, 2010)
Conserved protein-carbohydrate-lipid Pathogen Associated Molecular Patterns (PAMPs) interact with cells of the innate immune system to mediate antigen recognition and internalization and activation of immune cells. We examined if analogous ‘biomaterial associated molecular patterns’ composed of proteins, specifically their carbohydrate modifications, existed on biomaterials which can play a role in mediating the innate immune response to biomaterials. To probe for these carbohydrates in the adsorbed protein layer, as directed by the underlying biomaterial chemistry, self-assembled monolayers (SAMs) presenting –CH(3), -OH, -COOH or –NH(2) were pre-incubated with serum/plasma, and the presence of carbohydrate ligands of C-type Lectin Receptors (CLRs) was investigated using lectin probes in an Enzyme-linked Lectin Assays (ELLA). Presentation of CLR ligands was detected on control tissue culture polystyrene (TCPS). Absorbances of mannose or N-acetylglucosamine increased with decreasing incubating serum concentration; absorbances of sialylated epitopes or fucose remained unchanged. Absorbances of α-galactose or N-acetylgalactosamine decreased with decreasing incubating serum concentration; β-galactose was undetectable. Among SAM endgroups, pre-incubation with 10% serum resulted in differential presentation of CLR ligands; higher α-galactose on COOH SAMs than NH(2) or CH(3) SAMs, highest complex mannose on NH(2) SAMs and higher complex mannose on OH SAMs than CH(3) SAMs. Least sialylated groups were detected on CH(3) SAMs. In summary, biomaterial chemistry may regulate protein adsorption and hence unique presentation of associated carbohydrates. The ultimate goal is to identify the effects of protein glycosylations associated with biomaterials in stimulating innate immune responses.